PERTANGGUNG JAWABAN PIDANA NAKHODA KAPAL YANG BERLAYAR TANPA MEMILIKI SURAT IZIN BERLAYAR YANG MENGAKIBATKAN KEMATIAN (STUDI PUTUSANNOMOR 228/PID.SUS/2022/PN.TTE) - Sembiring, Windi Syahfitri Br.; Yunara, Edi; Nasution, Mirza (Smart Education, 2025)
Abstract: Criminal liability is the existence of an unlawful act, there is no word of forgiveness, capable of being competent in law, there is an error, there is no justification. An unlawful act is an act carried out by a person or group that is contrary to applicable regulations, an error is an act carried out either intentionally or unintentionally, a violation is an act that violates legal provisions (administrative in nature). In this study aims to answer the problem of How is the legal regulation for ship captains who sail without having a sailing license in Indonesia, How is the criminal liability for ship captains who sail without having a sailing license and result in death, How is the judge's consideration in applying criminal sanctions to the defendant in decision number: 228 / Pid.Sus / 2022 / PN.TTE. The regulation of shipping crimes is regulated in the Criminal Code and Law Number 17 of 2008 concerning Shipping which confirms the criminal liability of the captain as the party with full authority over the ship. In Decision Number 228/Pid.Sus/2022/PN.TTE regarding the sinking of the KM Cahaya Arafah, the judge sentenced the passenger to 4 years and 8 months in prison and a fine of Rp 500,000,000, a lighter sentence than the legal penalty due to consideration of extreme weather as a force majeure factor and the defendant's efforts to rescue passengers. This decision reflects the application of Gustav Radbruch's theory, namely balancing legal certainty, justice, and expediency, thus demonstrating the judge's role not merely as a mouthpiece for the law but also as an assessment of the humanitarian aspects and the law's benefits to society.Keyword: Criminal Liability, Ship Captain, Ship AccidentAbstrak: Pertanggung jawaban pidana itu adalah adanya perbuatan melawan hukum, tidak ada kata pemaaf, mampu cakap dalam hukum, adanya kesalahan, tidak ada alasan pembenar. perbuatan melawan hukum adalah tindakan yang dilakukans eseorang atau kelompok yang bertentangan dengan peraturan yang berlaku kesalahan adalah tindakan yang dilakukan baik sengaja maupun tidak sengaja pelanggaran adalah tindakan yang melanggar ketentua hukum (bersifat administratif). Dalam penelitian ini bertujuan untuk menjawab permasalahan Bagaimana pengaturan hukum terhadap nakhoda kapal yang berlayar tanpa memiliki surat ijin berlayar di Indonesia, Bagaimana pertanggung jawaban pidana terhadap nakhodah kapal yang berlayar tanpa memiliki surat ijin berlayar dan mengakibatkan kematian,Bagaimana pertimbangan hakim dalam menerapkan sanksi pidana terhadap terdakwa dalam putusan nomor: 228/Pid.Sus/2022/PN.TTE. Pengaturan tindak pidana pelayaran diatur dalam KUHP dan Undang-Undang Nomor 17 Tahun 2008 tentang Pelayaran yang menegaskan pertanggungjawaban pidana nakhoda sebagai pihak yang berwenang penuh atas kapal. Dalam Putusan Nomor 228/Pid.Sus/2022/PN.TTE terkait tenggelamnya KM Cahaya Arafah, hakim menjatuhkan pidana 4 tahun 8 bulan penjara dan denda Rp500.000.000, lebih ringan dari ancaman undang-undang karena mempertimbangkan faktor cuaca ekstrem sebagai force majeure serta adanya upaya terdakwa menyelamatkan penumpang. Putusan ini mencerminkan penerapan teori Gustav Radbruch, yakni menyeimbangkan kepastian hukum, keadilan, dan kemanfaatan, sehingga menunjukkan peran hakim tidak sekadar menjadi corong undang-undang tetapi juga menilai aspek kemanusiaan dan kemanfaatan hukum bagi masyarakat.Kata Kunci: PertanggungJawaban Pidana, Nakhoda Kapal, Kecelakaan Kapal